1987
DOI: 10.1021/ie00069a006
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of ASTM round-robin data on particle size using three different methods

Abstract: crease the reaction rate and also increase the possibility of further hydrogenation of the hydroxylamine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

1991
1991
2002
2002

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
2
1
0
Order By: Relevance
“…As mentioned earlier, the Microtrac Model 7795-11 was unable to measure particles greater than 176 /*m. The nonsphericity of the large particles was a major factor in the variation in particle size measured by these methods. These results were consistent with a published ASTM study (Flank, 1987).…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…As mentioned earlier, the Microtrac Model 7795-11 was unable to measure particles greater than 176 /*m. The nonsphericity of the large particles was a major factor in the variation in particle size measured by these methods. These results were consistent with a published ASTM study (Flank, 1987).…”
Section: Resultssupporting
confidence: 93%
“…Today most laboratories have abandoned dry sieving in favor of faster and less labor intensive techniques such as laser light scattering. This study, in agreement with other researchers (Flank, 1987;Frock et al, 1984; Novak and Thompson, 1986), has shown that the particle size determined by laser light scattering is greater than sieve values for cracking catalysts. Therefore, although refiners Figure 9.…”
Section: Microtrac/sieve Correlationsupporting
confidence: 93%
“…The HIAC Model PC-320 instrument is a single particle counter using the principle of light blockage (Allen 1981 p 585). Work done by the Particle Size Task Group of the ASTM Committee D-32 (Flank 1987) indicates the level of agreement that can be expected when comparing PSDS determined using different sizing methods. For example, it was reported that an electroconductive sensing method gave a volume median diameter (d5O) of 55.5 pm for a sample of a silica cracking catalyst for which the d50 results using laser.light diffraction and dry sieving were 65.7 pm and 66.3 pm respectively.…”
Section: Resultsmentioning
confidence: 99%